2022
DOI: 10.1142/s0218213022500373
|View full text |Cite
|
Sign up to set email alerts
|

Fraud Detection Using Large-scale Imbalance Dataset

Abstract: In the context of machine learning, an imbalanced classification problem states to a dataset in which the classes are not evenly distributed. This problem commonly occurs when attempting to classify data in which the distribution of labels or classes is not uniform. Using resampling methods to accumulate samples or entries from the minority class or to drop those from the majority class can be considered the best solution to this problem. The focus of this study is to propose a framework pattern to handle any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Several studies have explored imbalanced datasets in the context of different fraudulent cases, utilizing various resampling techniques and evaluation metrics (Rubaidi et al, 2022;Chen et al, 2021;Li et al, 2021;Mrozek et al, 2020;Bauder et al, 2018). Among the techniques used for handling imbalanced data were Random Undersampling (RUS), Random Oversampling (ROS), SMOTE, Borderline-SMOTE, Adaptive Synthetic Sampling (ADASYN), and cost-sensitive learning.…”
Section: Handling Of Imbalanced Datamentioning
confidence: 99%
“…Several studies have explored imbalanced datasets in the context of different fraudulent cases, utilizing various resampling techniques and evaluation metrics (Rubaidi et al, 2022;Chen et al, 2021;Li et al, 2021;Mrozek et al, 2020;Bauder et al, 2018). Among the techniques used for handling imbalanced data were Random Undersampling (RUS), Random Oversampling (ROS), SMOTE, Borderline-SMOTE, Adaptive Synthetic Sampling (ADASYN), and cost-sensitive learning.…”
Section: Handling Of Imbalanced Datamentioning
confidence: 99%
“…The classi er's performance is enhanced by integrating multiple classi ers. Other studies have employed NearMiss undersampling to address imbalances in nancial crime datasets (Mqadi et al, 2021;Rubaidi et al, 2022). The studies found that machine learning algorithms performed very well using the NearMiss undersampling technique.…”
Section: Nearmissmentioning
confidence: 99%
“…On the right is the decoder, which also has the two layers of the encoder, but between them there is an Encoder-Decoder Attention, which is used to help the decoder to focus on the relevant parts of the input sentence [57]. Training deep learning models [58] for fraud detection requires substantial amounts of labeled data, which can be a challenge due to the imbalance between normal and fraudulent instances [59]. Data preprocessing techniques, including resampling, oversampling, and undersampling, are employed to address this imbalance [60].…”
Section: Deep Learning Approaches To Fraud Detectionmentioning
confidence: 99%